STUDY THE EFFECT OF CARBON AND NITROGEN SOURCES ON GIBBERELLIC ACID PRODUCTION BY LOCAL STRAINS OF - Younis Al-Mashhadany; Nehan Al–Bayati (Mesopotamia Journal of Agriculture)
Two local strains of Fusarium moniliforme, were isolated from leaves and roots of maize plant. The two strains were compared for gibberellic acid production. The production of gibberellic acid by the local strain (1) was higher than strain (2). The strain (1) of F. moniliforme was chosen for the later experiments. The effects of culture components and conditions were studied at aiming to improve gibberellic acid production by the local strain (1). The optimum incubation period for the highest production of gibberellic acid was 9 days. The glucose, as a carbon source, gave the highest production of gibberellic acid reached 91.13 mg/liter especially at the concentration 2%. Ammonium nitrate, as a nitrogen source, gave the higher production of gibberellic acid reached 94.55 mg/liter and at the concentration 3 gm/liter. The technology of the spectrophotometer was used for the quantitative evaluation for gibberellic acid in the samples and at the wase longitude of 254 nanometer.